Evaluation of the efficacy of novaluron 0.2 % GR for the control of Aedes (Stegomyia) aegypti (Diptera) - Quimbayo F., Marcela; Pérez-Pérez, Juliana; Rodríguez-Gaviria, Paola A.; Amaya, Juan David; Rúa-Uribe, Guillermo L. (Revista Colombiana de Entomología, 2019)
Aedes (Stegomyia) aegypti is the main vector of dengue, zika and chikungunya in the Americas. These diseases have a significant impact on public health. According to the World Health Organization (WHO), controlling these diseases requires a comprehensive approach, and the control of larvae is a part of that strategy. Insect growth regulator (IGR) insecticides stand out as an efficient alternative for facilitating the control of Ae. aegypti at immature stages. The main goal was to evaluate the effectiveness of IGR novaluron 0.2 % GR, in the 50, 90, 95 and 99 lethal concentrations (LC) for fourth-instar larvae of Ae. aegypti in the laboratory. In field conditions, the percentage of inhibition of emergence was estimated by using the LC levels obtained in the laboratory through two methods of water management with refill and without refill in 40 L recipients. The study was carried out in 30 homes in a neighborhood with a high incidence of dengue in Medellin (Antioquia, Colombia). The bioassays completed indicated that LC 50, 90, 95 and 99 corresponded to 0.019, 0.055, 0.065 and 0.084 mg/L, respectively. The field results indicated that novaluron 0.2 % GR efficiently inhibited the emergence of adult Ae. aegypti, suggesting that the product has potential as a population regulator at very low concentrations. The product is considered extremely useful for programs to prevent and control dengue, zika and chikungunya.